2018
DOI: 10.3389/fchem.2018.00007
|View full text |Cite
|
Sign up to set email alerts
|

A Polyoxoniobate/g-C3N4 Nanoporous Material with High Adsorption Capacity of Methylene Blue from Aqueous Solution

Abstract: A polyoxoniobate/g-C3N4 nanoporous material with functional groups has been synthesized by using carbon nitride (g-C3N4) and hexaniobate (K8Nb6O19·10H2O, abbreviated as NbO) as precursors. The structure and compositions of the as-prepared nanomaterials were characterized by XRD, FT-IR, FESEM, TEM, and XPS. These two kinds of materials interact with each other forming a hybrid composite, which can be used as an adsorbent for removing a cationic dye (methylene blue, MB) from wastewater with excellent adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…The adsorption process was analyzed by the Langmuir (Equation 2) and Freundlich isotherm models (Equation 3) (Gan et al, 2018), and the equations are shown as follows:…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption process was analyzed by the Langmuir (Equation 2) and Freundlich isotherm models (Equation 3) (Gan et al, 2018), and the equations are shown as follows:…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the 1/n value of PhGs was calculated to be 0.22, which was <0.5. It indicated that the adsorption of the PhGs on the CMK-3 could take place easily (Fu et al, 2007; Gan et al, 2018). This indicated that the adsorption of PhGs on CMK-3 was not completely a physical adsorption process.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they can also be simply transformed to reactive forms by applying light and electricity (Gumerova and Rompel, 2018 ). The applications of polyoxometalate clusters as catalysts are many and varied, nonetheless they include mostly green H 2 O 2 -based epoxidation systems (Zhou et al, 2015 ), catalytic approaches to sustainable splitting of water (Long et al, 2010 ), and also photocatalysis in various photoredox systems e.g., the oxidation of alkanes, alkenes or alcohols as well as in the light-induced mineralization of several organic and inorganic contaminants (Shen et al, 2009 ; Streb, 2012 ; Wang et al, 2017 ; Gan et al, 2018 ; Li et al, 2018 ).…”
Section: Catalysis On Polyoxoniobatesmentioning
confidence: 99%
“…There are already examples of other than niobium-based polyoxometalates (Lefebvre, 2013 ). Only recently a functionalized polyoxoniobate/g-C 3 N 4 nanoporous material has been synthesized with carbon nitride (g-C 3 N 4 ) and hexaniobate (K 8 Nb 6 O 19 ·10H 2 O) as starting materials (Gan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%